Power loss reduction and voltage enhancement via distributed photovoltaic generation: Case study in North Cyprus. (October 2021) - Abujubbeh, Mohammad; Fahrioglu, Murat; Al-Turjman, Fadi
Abstract: Recently, power systems have witnessed a vast shift toward the integration of distributed generation systems (DGs), such as solar photovoltaic (PV) systems. The importance of planning DGs cannot be denied as they help to improve operations in the system and reduce the reliance on fossil fuel-based power generation methods. This paper proposes a new method for site and size selection of distributed PV systems considering system active power loss and nodal voltage profiles. The novelty of this work relies on nodal voltage magnitude deviations for PV siting and sizing criteria where PV DG sizes are weighted based on the voltage deviation index. This work includes a detailed case study performed on the Northern Cypriot power system with promising results that validate the proposed method against unweighted approaches.